THE IMPACT OF HIGHER EDUCATION ON ISLAMIC BOARDING SCHOOL - Ubaidillah Fadli Achmad; Sri Minarti (CV. TOTUS TUUS, 2026)
This study aims to analyze the impact of the presence of higher education institutions within Islamic boarding schools (pesantren) on the transformation of the education system, human resource development, and the social life of the surrounding community. The method used is a literature review by examining various scientific sources in the form of books, journals, previous research results, and official documents relevant to Islamic boarding school education and higher education. Data were analyzed descriptively and analytically through a process of grouping, comparing, and synthesizing concepts and expert findings. The results of the study indicate that higher education institutions within Islamic boarding schools have a positive impact in the form of integrating religious education and modern academics, improving the intellectual and professional quality of students and the Islamic boarding school community, and strengthening the role of Islamic boarding schools in community empowerment. However, this study also found challenges in the management of Islamic boarding school higher education institutions, particularly in maintaining a balance between traditional Islamic boarding school values ​​and the demands of higher education quality, so that an adaptive and sustainable management strategy is needed.